Who's Driving this Conversation? Systematic Biases in the Content of Online Consumer Discussions - Hamilton, Rebecca W.; Schlosser, Ann; Chen, Yu-Jen (Journal of Marketing Research, 2017)
When consumers post questions online, who influences the content of the discussion more: the consumer posting the question or those who respond to the post? Analyses of data from real online discussion forums and four experiments show that early responses to a post tend to drive the content of the discussion as much as or more than the content of the initial query. Although advice seekers posting to online discussion forums often explicitly tell respondents which attributes are most important to them, the authors demonstrate that one common online posting goal, affiliation, makes respondents more likely to repeat attributes mentioned by previous respondents, even if those attributes are less important to the advice seeker or support a suboptimal choice given the advice seeker's decision criteria. Firms “listening in” on social media should account for this systematic bias when making decisions on the basis of the discussion content.